Rancangan dan Pengujian Alat Bantu Kebocoran Ban Sepeda Motor - Aswan Munang; Dita Trianingrum (Infotekmesin, 2022)
Sustainable product design has a role in reducing environmental impacts and can provide economic and social benefits for stakeholders. Design is one way to make improvements and provide an overview of alternative solutions to problems. One of the problems of motorcycle users is experiencing the incidence of punctured tires. This research aims to design a tool to help users of automatic and manual motorcycles when a flat tire occurs. The tool design with dimensions of 160 mm x 190 mm x 100 mm uses a 2 mm iron plate as the mainframe, rubber-type wheels on the front and live caster on the back, and stainless steel for bolts and nuts. Testing the tire leak tool uses three motorcycles with automatic and manual types that have an engine capacity of up to 110 cc, and has a wheel size of 62.09 mm for automatic motorbikes and 65.79 mm for manual motorbikes. The test results showed it function well. The tool is stable and safe when used at a speed of 20 km/hour. The tire leak tool can be used on various types of road surfaces and can withstand passenger loads of up to 65 kg. The trial process was carried out 7 times in the environment around the Purwokerto Telkom Institute of Technology campus with up and down road surfaces and various variations of bends. The tool design is easy to install on leaking wheels and is convenient to carry on the go. A tire leak tool can be used as an alternative for motorcyclists when a flat tire occurs, especially automatic and manual motorbikes.